The instant and its shadow a story of photography - Bailly, Jean-Christophe 1949- (Fordham University Press, 2020)
A compelling and innovative reflection on the way photography captures and condenses timeTwo photographs, connected by a ladder, separated by a century. First, William Henry Fox Talbot photographed a faithfully realistic image of a ladder against a haystack in the English countryside.One hundred years later, an anonymous photographer captured another ladder, "photographed" alongside an incinerated man by the blinding light of the atomic bomb. These two images underpin a poetic and theoretical reflection on the origins of photographic technique, the imaginative power of montage, and the relation of photography to time itself in Jean-Christophe Bailly’s The Instant and Its Shadow, translated into English for the very first time.A rare find of intellectual caliber and theoretical rigor, The Instant and Its Shadow pursues a unique and powerful reflection on the first hundred years of photography’s history and on the essence of the photographic art in general.